2008
DOI: 10.1007/s00535-008-2182-9
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, single-blind trial comparing wireless capsule endoscopy and double-balloon enteroscopy in patients with obscure gastrointestinal bleeding

Abstract: Our results demonstrate the superiority of CE in detecting abnormal lesions, and the superiority of DBE in endoscopic management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
1
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 21 publications
3
66
1
11
Order By: Relevance
“…Thus, the incidence of small-intestinal mucosal injury was clearly increased in rheumatoid arthritis patients who used NSAIDs. At our hospital (Osaka Medical College Hospital), we found that approximately 10.3% had small-bowel injuries associated with NSAIDs among patients who received VCE or BE for obscure gastrointestinal bleeding (OGIB) ( Table 1), compatible with other reports [2]. With the ease of small intestine examination, we are beginning to see a relatively high incidence of small-intestinal mucosal injuries due to NSAIDs, and measures for remedying such injuries have become urgent.…”
Section: Present Status Of Small Intestinal Mucosal Injury Caused By supporting
confidence: 78%
See 2 more Smart Citations
“…Thus, the incidence of small-intestinal mucosal injury was clearly increased in rheumatoid arthritis patients who used NSAIDs. At our hospital (Osaka Medical College Hospital), we found that approximately 10.3% had small-bowel injuries associated with NSAIDs among patients who received VCE or BE for obscure gastrointestinal bleeding (OGIB) ( Table 1), compatible with other reports [2]. With the ease of small intestine examination, we are beginning to see a relatively high incidence of small-intestinal mucosal injuries due to NSAIDs, and measures for remedying such injuries have become urgent.…”
Section: Present Status Of Small Intestinal Mucosal Injury Caused By supporting
confidence: 78%
“…BE was superior to VCE in the diagnosis of relatively large lesions as polyps. On the other hand, small lesions such erosions and red spots were more often detected by VCE than BE [2]. In addition, we do not know which is higher, the detection ability of biomarkers or that of endoscopy.…”
Section: Diagnosis Of Nsaids-induced Small Intestinal Injurymentioning
confidence: 81%
See 1 more Smart Citation
“…Guidelines developed by Gerson et al are presented here as an example. [8][9][10][11][12][13][14][15][16][17][18] Our algorithm is shown in Figure 5.…”
Section: Yes Nomentioning
confidence: 99%
“…General consensus today is that early diagnosis by CE can be followed by DBE findings, combined with interventional enteroscopy by the same method. (Kameda N et al, 2008;Marmo R et al, 2007) 6.2 Capsule endoscopy in Crohn's disease In Crohn's disease, patients often experience pain, diarrhea and weight loss, non-specific symptoms that do not correlate with the negative results from usual imaging investigations. (Kornbluth A et al, 2005) A consensus panel suggested that further investigation by CE is useful when patients display at least two of these symptoms.…”
Section: Diagnostic Yield Comparison With Other Investigations and mentioning
confidence: 99%